Analysis of the Carrying Capacity of Proboscis Monkey Habitat on Bakut Island, South Kalimantan, Based on Leaf Area Index - Fithria, Abdi; Kanti, Rina; Rezekiah, Arfa Agustina; Ali, Syamani D; Prihatiningtyas, Eva; Azizah, Noor Aida; Setiawan, Eko Budi; Pribadi, Ahdiyaka Jayasukma; Kamil, Naufal Noor (Jurnal Penelitian Kehutanan Wallacea, 2025)
Bakut Island is one of the conservation forest areas in South Kalimantan. This island is the habitat of proboscis monkeys, and the proboscis monkey population is increasing from year to year. Therefore, it is estimated that one day the proboscis monkey habitat on Bakut Island will be over capacity. This study aims to estimate how long the population of proboscis monkeys on Bakut Island Nature Tourism Park can survive there by examining the amount of food the island's vegetation can produce. Proboscis monkey feed itself is estimated using the Leaf Area Index (LAI). LAI was extracted using UAV imaging and NICFI multitemporal imagery. Meanwhile, the carrying capacity of the proboscis monkey habitat is assessed using the quantity of consumption of the proboscis monkey population relative to food availability. Simulations of the carrying capacity of proboscis monkey habitat into the future were carried out using projections of the future proboscis monkey population and LAI growth. The entire computational process of simulating habitat carrying capacity is carried out using the Python language. The results of the analysis show that Bakut Island is only able to support proboscis monkey habitat until 2038. In that year, the proboscis monkey population on Bakut Island is projected to number 1,290 individuals. After 2038, the predicted amount of feed needed by the proboscis monkey population will exceed the feed available on Bakut Island. The limitation of this research is that it only uses one parameter to assess the carrying capacity of proboscis monkey habitat, namely food availability. There are still other parameters that have not been accommodated, including the home range and trees for nests.